THE RELATIONSHIP OF TOILET TRAINING TOWARD TOILET TRAINING BEHAVIOUR OF PRE-SCHOOL CHILDREN IN EARLY CHILDHOOD EDUCATION PROGRAMS (PAUD) (1-3 YEARS) AT PUSPA BANGSA KINDERGARTEN BOGOR : HUBUNGAN PENGETAHUAN TENTANG TOILET TRAINING DENGAN PERILAKU MELATIH TOILET TRAINING PADA ANAK USIA TODDLER (1-3 TAHUN) DI PAUD PUSPA BANGSA KOTA BOGOR - Rosalina Rosalina (Wijaya Husada, 2018)
In Indonesia an estimated number of infants up to 30% of the 250 million population of Indonesia, and according to the Household Health Survey (Survey) estimated the number of infants nationwide were hard to control bowel and bladder in the toddler to preschool reach 75 million children. The Objective to determine the relationship of knowledge about toilet training to conduct training toilet in toddler (1-3 years) in Puspa Bangsa Kinder Garden Bogor 2015. The Methods used a descriptive analytic research with cross sectional study design. A total sampling with a sample size was 46 Instrument, this study using a questionnaire. Results people who have a good knowledge of as many as 21 people (45.7%) and who has sufficient knowledge of 15 people (32.6%) while the less knowledgeable 10 people (21.7%). Statistical test results obtained value ρ = 0.004, which means there is a significant relationship of two variables. In conclusion, there were a relationship between knowledge about toilet training to conduct training toilet training in toddler (1-3 years) at Puspa Bangsa KinderGarten Bogor.